Extending the overwork of women in Upper Guinea: Mobiliy as a research mode of autonomy? - Toure, Mabetty (Geographicalia, 2018)
In Upper Guinea, gender relations are marked by inequality and domination. Reports at work highlight the importance and diversity of the forms of overwork and exploitation of women and cadets by men. The structure of the Malinke society makes it possible to establish the place of each member in the decision-making and execution of works in the fields. Agriculture is practiced differently according to sex and age, which creates unfavorable balance of power for women who do not have access to means of production and do not control resources. This article proposes to show that, despite immense efforts in the field of the production of family wealth, where women value their labor power and that of children, their place does not correspond to their economic contribution. Victims of extortion from overwork, they develop activities related to domestic ones such as the exploitation of néré or shea through mobility to meet the needs of their families.
Keywords: Extortion, genre, movility, autonomy